Strategi Para Konten Kreator Untuk Meningkatkan Penghasilan di Era Digitalisasi Melalui Live Tiktok - Siti Rika Nurani; Maya R Atmawinata (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the strategies implemented by content creators to increase income through the live streaming feature on the TikTok platform. The live streaming phenomenon has become a rapidly growing trend, especially among the younger generation, and provides new economic opportunities for individuals who are able to utilize the digital platform creatively. This study used a descriptive qualitative approach with data collection through in-depth interviews with five informants who actively live stream on TikTok. The results show that TikTok's For You Page (FYP) algorithm plays a significant role in expanding audience reach and attracting new viewers, thus contributing directly to increased creator income. Some commonly implemented strategies include creating interactive content such as challenges, intensive interaction with audiences during live broadcasts, consistent personal branding development, and cross-promotion through other social media. These strategies aim to attract viewers and encourage them to provide financial support through TikTok's gift feature and donations from third-party platforms such as Saweria and Trakteer. Furthermore, creators also build loyal fan communities to maintain long-term engagement and strengthen their digital identity. However, creators face several challenges, particularly related to TikTok's fairly strict content moderation policies, which can limit freedom of expression during live streaming. In response to these challenges, some creators have begun diversifying their platforms by expanding their broadcasts to other media outlets, such as YouTube Live or Instagram Live. This research provides a comprehensive overview of the dynamics of the digital creator economy in the era of platformization and can serve as a reference for aspiring content creators and researchers interested in the digital economy and social media.